2023
DOI: 10.3389/fimmu.2022.1103533
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and sequelae of epidermolysis bullosa acquisita: A propensity-matched global study in 1,344 patients

Abstract: Identification of risk factors and sequelae of any given disease is of key importance. For common diseases, primary prevention and disease management are based on this knowledge. For orphan diseases, identification of risk factors and sequelae has been challenging. With the advent of large databases, e.g., TriNetX, this can now be addressed. We used TriNetX to identify risk factors and sequelae of epidermolysis bullosa acquisita (EBA), a severe and orphan autoimmune disease. To date, there is only enigmatic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…EBA is a relatively rare AIBD resulting from the immunoglobulin G antibody against the type VII collagen within the anchoring fibril. The association between EBA and SLE was well recognized 40 . EBA was also found to share a similar autoantibody with bullous LE 53 .…”
Section: Ra Le Dm/pm Ss Vitiligo Mg Aitd Aamentioning
confidence: 86%
See 2 more Smart Citations
“…EBA is a relatively rare AIBD resulting from the immunoglobulin G antibody against the type VII collagen within the anchoring fibril. The association between EBA and SLE was well recognized 40 . EBA was also found to share a similar autoantibody with bullous LE 53 .…”
Section: Ra Le Dm/pm Ss Vitiligo Mg Aitd Aamentioning
confidence: 86%
“…The association between EBA and SLE was well recognized. 40 EBA was also found to share a similar autoantibody with bullous LE. 53 Bullous LE is an uncommon variant of SLE, with cutaneous blisters appearing more in sun-exposed areas, such as face, and some on mucosal surfaces.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Recently, it has been found that 55 different diseases had significantly different prevalences among EBA patients compared to the general population. Of these, 23 diseases were identified as risk factors for EBA ( 8 ). In these cases, alternative therapy may be required, as exemplified by our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although IBD has long been recognized as a risk factor for EBA ( 2 , 14 17 ), recent research on medical records of 1344 EBA cases has challenged this association. The authors did not identify inflammatory bowel diseases as risk factors or sequelae of EBA ( 8 ).…”
Section: Discussionmentioning
confidence: 99%